2008
DOI: 10.1002/sia.2924
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties of polypropylene following a novel industrial surface‐treatment process

Abstract: Polypropylene (PP) is used in many automotive applications where good paint adhesion is of primary importance. PP is widely known for its low surface energy which impacts negatively on its adhesion strength. PP surfaces were modified using a new industrial surface-treatment process known as the Accelerated Thermo-molecular adhesion Process (ATmaP). ATmaP grafts functional groups to the polymer surface derived from an atomised and vapourised nitrogen-containing coupling agent. The surface properties and adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
0
16
0
2
Order By: Relevance
“…Moreover, complex R-NH 2 and RO-NH 2 functional groups could be found, which might be the products of the reaction between broken chains from PP backbones and the CH 3 CN solvent. 49 In a brief summary, the ageing process of the SCs was irreversible because of those side reactions among the key components with the electrolyte as the main linking medium. The consequent decline of electrical conductivity, blockage of effective pores in AC and PP separators, decrease of specific surface area, and delamination between the current collector and AC layer would definitely deteriorate the electrochemical performance of SCs and eventually resulted in their failure.…”
Section: Chemical Characterizationsmentioning
confidence: 99%
“…Moreover, complex R-NH 2 and RO-NH 2 functional groups could be found, which might be the products of the reaction between broken chains from PP backbones and the CH 3 CN solvent. 49 In a brief summary, the ageing process of the SCs was irreversible because of those side reactions among the key components with the electrolyte as the main linking medium. The consequent decline of electrical conductivity, blockage of effective pores in AC and PP separators, decrease of specific surface area, and delamination between the current collector and AC layer would definitely deteriorate the electrochemical performance of SCs and eventually resulted in their failure.…”
Section: Chemical Characterizationsmentioning
confidence: 99%
“…The response of the bond strength to two variables was studied, based on previous experience,19, 20 preliminary observations and trials. The RF power ( x 1 ) measured in Watt, and treatment time ( x 2 ) measured in minutes were selected as the parameters of interest.…”
Section: Experimental Partmentioning
confidence: 99%
“…This claim is very significant for industry as it could reduce costs and time‐consuming surface cleaning processes. In a previous study it was shown that ATmaP was able to modify the surface of thermoplastics chemically through the grafting of an atomized and vaporized nitrogen‐based coupling agent (n‐methylpyrrolidone) resulting in increased adhesion strength 35…”
Section: Introductionmentioning
confidence: 99%